Primary Cutaneous Vasculitis Masquerading as Drug Induced following Aspirin Desensitization. (24th November 2013) - Al-Nesf, Maryam Ali; Mobayed, Hassan M. S.; Raza, Tasleem
Abstract : Aspirin-exacerbated respiratory disease (AERD) is a well-known clinical condition. Aspirin desensitization followed by daily aspirin therapy is the treatment of choice. We report a challenging case of primary cutaneous vasculitis following aspirin desensitization in a patient with AERD. The vasculitis was likely suppressed with higher dose systemic steroid use to control asthma. Aspirin desensitization led to improved asthma control and steroid reduction, which led to manifestation of prior suppressed cutaneous vasculitis. In our case, there was no evidence of systemic involvement and the patient had a favorable outcome with appropriate therapy.